Synthesis strategies of optimized cathodes and mechanisms for zinc ion capacitors. (December 2022) - Qu, Keqi; Lu, Xuejun; Huang, Zhanhua; Liu, Jian
Abstract: Zinc ion capacitors (ZICs) have been regarded as a new generation of energy storage devices with the integration of zinc ion batteries (ZIBs) and supercapacitors (SCs) due to their high safety, low cost, satisfactory voltage range, and long-term lifespan. In formulating cathode materials with high capacities and favorable compatibility with the anodes, factors such as microstructure, surface functionalization, and material internal adaptability have become the priority considerations for researchers. Cathode materials (capacitor or battery-type materials) have been extensively studied and explored as common electrode materials in energy storage devices, taking advantage of their multi-selectivity and high tunability. Recently, several perspectives have summarized the application and development prospects of cathode materials in metal-based hybrid capacitors (MHCs). Nevertheless, ZICs are still a relatively new research topic that requires further attention and discussion on the electrodes themselves and how to improve their overall electrochemical performance. This review systematically introduces the basic composition and types of ZICs. Furthermore, the physical and chemical characteristics of cathode materials in different dimensions and their induced electrochemical performance are presented with dimensional boundaries. Strategies to improve the electrochemical performance of cathode materials and the energy storage mechanism of ZICs are analyzed in detail. Finally, the proposed viewpoints and the future challenges of ZICs are generalized. This paper provides references and insights for designing novel cathode materials for the better development of ZICs. Graphical abstract: Image 1 Highlights: Structure modification of cathodes regulates physicochemical properties and capabilities. Advanced cathodes and ZICs system design improve electrochemical performance. The cathodes affect the working mechanism in ZICs. The trends and prospects for ZICs are discussed.